Assessment of Serum Macrophage Migration Inhibitory Factor (MIF) as an Early Diagnostic Marker of Leptospirosis - Sumaiya, Krishnamoorthi; Akino Mercy, Charles Solomon; Muralitharan, Gangatharan; Hajinur Hirad, Abdurahman; Alarfaj, Abdullah A.; Natarajaseenivasan, Kalimuthusamy (Frontiers in Cellular and Infection Microbiology, 2022)
The search for valuable early diagnostic markers of leptospirosis is ongoing. The aim of the present study is to evaluate the diagnostic value of macrophage migration inhibitory factor (MIF) for leptospirosis. MIF is an immunoregulatory cytokine secreted by variety of cell types, involved in immune response and pathogenesis of various diseases, and previously described as severity predictor of diseases. Samples of 142 leptospirosis cases, 101 other febrile cases and 57 healthy controls were studied. The prevalence of leptospirosis was 47.3%. Autumnalis, Australis, and Canicola were the highly prevalent leptospiral serovars with the microscopic agglutination test (MAT) titres in the range of 1:80 to 1:2560. MIF enzyme linked immunosorbent assay (ELISA) was carried out to measure the serum MIF levels. We found that serum MIF level (Median (Interquartile Range)) was significantly (p<0.001) elevated in different clinical forms of leptospirosis including febrile illness (7.5ng/mL (5.32-8.97)), pulmonary hemorrhages (13.2ng/mL (11.77-16.72)), Weil’s syndrome (8.8ng/mL (7.25-9.95)) and renal failure (8.6ng/mL (7.18-10.5)) than healthy controls (0.65ng/mL (0.5-1.1)). Serum MIF had sensitivity, specificity, positive predictive value, and negative predictive value of 100%, >90%, >90%, and 100% respectively. Receiver operating characteristics (ROC) analysis revealed that serum MIF level between leptospirosis cases and control subjects with an area under the curve (AUC) value of >0.9 (p<0.0001). In leptospirosis patients, elevation of serum MIF was significantly (p<0.001) higher in severe cases with organ dysfunction (10ng/mL (7.8-14.5)) than mild febrile cases (7.5ng/mL (5.32-8.97)) with the difference of 2.5 indicates that serum MIF acts as predictor of leptospirosis severity. Pearson correlation test demonstrated that serum MIF level was strongly correlated (r=0.75, p<0.0001) with disease progression. The median lethal dose (LD50) of leptospiral lipopolysaccharide (LPS) in BALB/c mice was determined to be 20mg/kg, which give rise to endotoxemia. Leptospiral LPS triggers the upregulation of MIF expression at 24h post infection and reached the peak level at 24h post treatment in THP-1 cells and showed elevated MIF expression in different tissues of BALB/c mice at the early stage of infection. Taken together, MIF is an early phase cytokine which will serve as a rapid diagnostic marker of leptospirosis.